Nurse management of minor problems in primary care emergencies: a non-randomized controlled trial - Jordi Estarlich-Corominas; Neus Soler-Abril; Anna Casanellas-Chuecos; Sara Becerra-Corzo; Andrea Sofia Bianco; Pere Torán-Monserrat; Rosa García-Sierra (BMC Nursing)
Abstract Background Health systems must implement strategies to adapt to the high demand in primary care caused by social changes. Since 2009, the Catalan Institute of Health has been expanding the Nurse Demand Management programme through which nursing autonomously addresses minor health problems. This study aims to analyse whether this programme is a factor in improving the efficiency and quality of care in a primary care emergency centre. The results come from a non-randomised controlled experimental study that tested the implementation of the programme applied to an experimental group treated by nurses versus a control group treated by doctors. The study was approved on 14 July 2022 by the Research Ethics Committee of the Jordi Gol University Institute following the guidelines of the TREND statement. Results A total of 312 patients were included in the study, all of whom came to the emergency centre with five types of minor problems. Exactly half (156) were seen by nurses and half were seen by doctors. The experimental group had an average waiting time of 15.1 min and the control group 33.25 min. There was no significant difference in the assessment of the quality of care received and there were no differences in the total number of consultations for the same problem. There were fewer prescriptions given out by nurses, with an average of 1.79 medicines per participant versus 2.26 medicines prescribed by doctors. The results of the study suggest that the Nurse Demand Management programme was a factor in improving the efficiency and in the emergency centre. Nurse resolution capacity, after applying algorithms, offered quality care, with fewer prescriptions and good patient satisfaction without increasing the total number of consultations due to the same problem. Trial registration The protocol for the current study was registered at Clinicaltrials.gov, with identification NCT06298240, retrospectively registered February 29, 2024.